The Ordinances of the City of Richmond, Ch. 62, Concerning Powder, §1-7. - (:unkn) unknown (My University, 1869)
Not more than fifty pounds of powder shall be transported in the city at one time, except by a military company, or in a vehicle constructed as the Engineer of the city shall prescribe.
Keywords: GUNPOWDER - TRANSPORTATION